GROUNDWATER POTENTIAL IN LY SON ISLAND AND ORIENTATION OF EXPLOITATION AND USE - Dan, Nguyen Van; Thong, Bui Xuan; Hoa, Nguyen Thi Khanh (Vietnam Journal of Marine Science and Technology, 2018)
Ly Son is an island district of Quang Ngai province consisting of two islands: Big island and small island. With an area of about 8.7 km2, big island has 2 aquifers. The unconsolidated formation aquifer (qh) has a narrow distribution in the coastal strip with a small thickness, most of the area of the groundwater is saline, meaningless for water supply. The basaltic eruption formation aquifer (βq) is widely distributed, occupying 85% of the island’s area and has moderate water potential and there is capability for construction of public wellfields with small scale of water supply. Potential for groundwater reserves in the βq aquifer is quite abundant: Exploitation potential reserves is 12,638 m3/day, the exploitable reserve is 5,203 m3/day, the exploited reserve classified as class C1 is 3,531 m3/day, enough to meet the current and future water demand in the island. Groundwater exploitation in the island is mainly spontaneous, leading to the risk of salinity intrusion, contamination. It is necessary to rectify this situation with public exploitation solutions and have solutions to protect and develop water resources in a rational way to ensure sustainable development.